2015
DOI: 10.3758/s13421-015-0528-0
|View full text |Cite
|
Sign up to set email alerts
|

Inferential revision in narrative texts: An ERP study

Abstract: We evaluated the process of inferential revision during text comprehension in adults. Participants with high or low working memory read short texts, in which the introduction supported two plausible concepts (e.g., 'guitar/ violin'), although one was more probable ('guitar'). There were three possible continuations: a neutral sentence, which did not refer back to either concept; a no-revise sentence, which referred to a general property consistent with either concept (e.g., '…beautiful curved body'); and a rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
45
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(65 citation statements)
references
References 52 publications
10
45
1
Order By: Relevance
“…These effects signaled greater ease of integration in the expected condition, demonstrating that, in their L1, comprehenders were able to revise their initial prediction when previous alternative inferential information had been provided. Importantly, this result also replicates the findings of the original study in L1 comprehension (Pérez et al, 2015), where higher WM readers showed less negativity in the expected compared to the other two conditions. In the L2, by contrast, the expected condition was only marginally less negative than the unexpected, and no differences were found between the uncertain and the other two conditions.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These effects signaled greater ease of integration in the expected condition, demonstrating that, in their L1, comprehenders were able to revise their initial prediction when previous alternative inferential information had been provided. Importantly, this result also replicates the findings of the original study in L1 comprehension (Pérez et al, 2015), where higher WM readers showed less negativity in the expected compared to the other two conditions. In the L2, by contrast, the expected condition was only marginally less negative than the unexpected, and no differences were found between the uncertain and the other two conditions.…”
Section: Discussionsupporting
confidence: 89%
“…A paradigm developed to investigate inferential revision is the situation model revision task (Pérez et al, 2015). In this task, participants are presented with short narrative texts (see Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, our second goal was to assess whether individual differences in EVALUATION AND REVISION OF INFERENCES 6 working memory associated with the revision process are related to working memory differences. Given previous work, we anticipated a closer association with verbal working memory (Cain, 2006;Pérez et al, 2015;Pimperton & Nation, 2010).…”
Section: Introductionmentioning
confidence: 96%
“…These studies have usually used a sentence-by-sentence procedure, measuring reading times for the whole sentence and/or answers to comprehension questions (e.g., Albrecht & O'Brien, 1993;Rapp & Kendeou, 2007;O'Brien et al, 1998;Zwaan & Madden, 2004). A recent study by Pérez, Cain, Castellanos and Bajo (2015) measured on-line processing in evaluation and revision by recording event-related potentials, but they did so only for a final disambiguating sentence, without providing the opportunity to reread the text after encountering the mismatch or before answering the comprehension sentence. To capture the interplay between mismatch EVALUATION AND REVISION OF INFERENCES 5 detection (evaluation) and mismatch regulation (revision) in the construction of the situation model, it is important to measure reading as it happens, across the whole text (not just an isolated sentence) together with the comprehension sentence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation